Cystic lesion in parotid region: an unexpected diagnosis. Issue 8 (25th August 2022) - Saraniti, Carmelo; Patti, Gaetano; Rodolico, Vito; Verro, Barbara
Abstract : Benign tumours of salivary glands represent 2%–3% of all tumours and parotid gland is most often affected. Keratocystoma is a rare benign tumour with multilocular cystic lesions filled with keratin materials. Histologically, it is characterised by solid epithelium islands containing keratinised lamellae with multicystic spaces. We report a case of a woman in her mid-70s with painless mass in her left parotid gland which increased in size over 1 year. Ultrasound scan revealed a 38×20 mm diameter hypoanechoic mass. Neck CT with contrast medium and fine needle aspiration were performed with diagnostic hypothesis of Warthin tumour. So, extracapsular parotid dissection with no facial nerve damage was performed. Histological examination revealed a keratocystoma. The patient had a 16-month follow-up without signs of relapse or malignancy. Despite its rarity, keratocystoma must be considered among the possible differential diagnostic hypotheses when we find parotid masses, to ensure the best treatment to the patient.